2004
DOI: 10.1023/b:ectx.0000037193.28684.05
|View full text |Cite
|
Sign up to set email alerts
|

Coumaphos Distribution in the Hive Ecosystem: Case Study for Modeling Applications

Abstract: Pesticides are currently used inside hives, against the honeybee parasite Varroa destructor, producing unwanted contamination effects. To assess the distribution and fate of one of these pesticides (coumaphos), two experimental hives were treated with Perizin (the commercial product containing the active ingredient coumaphos). Samples of honey, wax, pollen, adult bees and larvae taken before treatment and up to 104 days afterwards, showed diffuse contamination. Wood hedges and wax bridges, where the pesticide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 1 publication
2
63
0
2
Order By: Relevance
“…menthol, thymol. (Tremolada et al, 2004) assessed the possible distribution of coumaphos applied as Perizin within a beehive following a varroacide treatment with 32mg/hive. Based on the vapour pressure of 0.013 mPa at 20C this equates to an air saturation of 1.9 μg/m3 and the volume of air within a hive of 0.2m3 gives a saturation in the air of 0.000001%.…”
Section: Inhalation Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…menthol, thymol. (Tremolada et al, 2004) assessed the possible distribution of coumaphos applied as Perizin within a beehive following a varroacide treatment with 32mg/hive. Based on the vapour pressure of 0.013 mPa at 20C this equates to an air saturation of 1.9 μg/m3 and the volume of air within a hive of 0.2m3 gives a saturation in the air of 0.000001%.…”
Section: Inhalation Exposurementioning
confidence: 99%
“…The majority of published studies relate to in-hive treatments with varroacides and antibiotics and solely measured residues in honey intended for human consumption (e.g. (deGrandi-Hoffman and Hagler, 2000;Nakajima et al, 1997;Nakajima et al, 1998;Bonzini et al, 2011;Tremolada et al, 2004;Tremolada et al, 2011). However, there are a small number of studies which specifically address the distribution of incoming contaminated nectar within hives including Nixon and Ribbands (1952), who demonstrated that releasing just six foragers fed with radiolabelled sμgar into a colony resulted in about 20% of the workers in the brood area receiving some labelled food within 3.5 hours and this included nurse bees which demonstrated the potential exposure of brood.…”
Section: Distribution Around Hivesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also used widely to control the mites in beekeeping, and accumulates in the wax of the comb at high concentrations (Bogdanov et al, 1998;Wallner, 1999;Tremolada et al, 2004). It is one of the most common pesticides found in honeybee colonies.…”
Section: τ-Fluvalinatementioning
confidence: 99%
“…Currently, the main biological factor harming honey production in Uruguay is the prevalence of varroosis (the infection of hives caused by the mite Varroa destructor) . However, efforts to control mites with synthetic miticides (normally with xenobiotic characteristics) have led to two additional problems, that is, an increase in the risk of selecting resistant V. destructor strains (Lodesani et al, 1995;Elzen et al, 2000;Thompson et al, 2002;Pettis, 2004) and an increase in the risk of hive products by miticides (e.g., coumaphos) (Wallner, 1999;Tremolada et al, 2004). More specifically, the first problem has led to a progressive decrease in the efficacy of synthetic acaricides to control resistant V. destructor strains.…”
mentioning
confidence: 99%